PERAN PENDAMPING PROGRAM KELUARGA HARAPAN DI KELURAHAN PASAR AMBACANG KECAMATAN KURANJI KOTA PADANG - Silvia, Niken; Rinel Fitlayeni; Wibi Wijaya (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
The background of this research is the extent of the role of assistants in Pasar Ambacang Village, Kuranji District, Padang City. Mentors as spearheads for PKH recipients. This study uses structural functional theory according to Talcott Parsons. This discussion of Parsons' structural functionalism will begin with four AGIL schemes. The approach used is descriptive qualitative. While the type of research is a case study. The data collection carried out in this research is the method of observation, interviews, and document studies. Primary data in the form of data obtained directly by the author from the results of observations and interviews with research informants as many as 14 people. While the types of the results of this study indicate 5 roles of PKH facilitators in Pasar Ambacang Village, namely: 1) The role of facilitator is to provide motivation, opportunities and support for PKH recipient communities. 2) Role as a Advisor provides positive input based on experience. 3) Role as Liaison in several related parties. 4) Role as a mobilizer in PKH Program activities. 5) Role as an Evaluator to see the level of success.